Structural analysis and tectonic interpretation of the Thabazimbi Kumba Iron Mine region using the Operational Land Imager (OLI) and Thermal Infra Red Sensor (TIRS) LANDSAT 8 satellite imagery - Altermann, Wladyslaw, 1954- (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2019.